2013
DOI: 10.1080/10810730.2013.821553
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Fatalism and Increased Prevention Behavior After Two High-Profile Lung Cancer Events

Abstract: The positive impact of media coverage of high-profile cancer events on cancer prevention behaviors is well-established. However, less work has focused on potential adverse psychological reactions to such events, such as fatalism. Conducting 3 studies, the authors explored how the lung cancer death of Peter Jennings and diagnosis of Dana Reeve in 2005 related to fatalism. Analysis of a national media sample in Study 1 found that media coverage of these events often focused on reiterating the typical profile of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Past research has found that media exposure—including exposure to health information via newspaper, television, the Internet, and other media sources—can facilitate cancer information seeking [ 27 , 79 , 109 ]. However, previous studies have focused on the impact of media content and framing on health information-seeking behavior [ 25 ] rather than the impact of different types of media exposure on information-seeking behavior.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Past research has found that media exposure—including exposure to health information via newspaper, television, the Internet, and other media sources—can facilitate cancer information seeking [ 27 , 79 , 109 ]. However, previous studies have focused on the impact of media content and framing on health information-seeking behavior [ 25 ] rather than the impact of different types of media exposure on information-seeking behavior.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…In most subpopulations, heart disease incidence is higher than cancer incidence, 1 yet laypeople may think the reverse given extensive cancer exposure 2 such as the “pink ribbon” campaign and celebrity deaths (e.g., Peter Jennings 3 ). People often overestimate their own cancer risk 4 and thus may also overestimate its relative prevalence.…”
Section: Introductionmentioning
confidence: 99%